Answer:
.5(-9x - 55)
Step-by-step explanation:
1.5(2x - 5) - ________ = 2.5(3x + 8)
-1.5(2x - 5) -1.5(2x - 5), [subtract 1.5(2x - 5) from both sides]
--------------------------------------------
(-)________ = 2.5(3x + 8) - 1.5(2x - 5), [result]
(-)*(-)________ = (-)*[2.5(3x + 8) - 1.5(2x - 5)], [multiply (-) to both sides]
---------------------------------------------
________ = 1.5(2x - 5) - 2.5(3x + 8), [result]
________ = 3x - 7.5 - 7.5x - 20, [multiply through]
________ = -4.5x - 27.5, [add like terms]
________ = .5(-9x - 55), [factor out a .5 to create the form of the original equation]
Therefore 1.5(2x - 5) - .5(-9x - 55) = 2.5(3x + 8)